Adverse Child Events (ACES) and their Negative, Long-Term: Impacts on Mental, Behavioral, and Physical Health - Hoffman, Kim (Sílex, 2022)
Exposure to adverse childhood experiences (ACEs) is violent, stressful, or traumatic experiences undergone in childhood. It is estimated that about 16 % of adults in the U.S. have had four or more types of adverse childhood experiences, which are significantly associated with poorer health outcomes, health risk behaviors, and socioeconomic challenges. Research has found a relationship between exposure to ACEs and morbidity and mortality later in life. The high prevalence of ACES, along with their effect on health, social, and medical costs has led this issue to be a matter of public health globally. This paper discusses the impact of ACES, how ACES are measured, and the linkages ACES have to different health outcomes. Future research is needed to better understand adverse childhood events, specifically how to assess, address and prevent these experiences in children.